2021
DOI: 10.1063/5.0044419
|View full text |Cite
|
Sign up to set email alerts
|

Voltage–current characteristics of low-pressure discharges in vapors of several alcohols

Abstract: In this paper, we present the results for voltage-current (V-i) characteristics of dc lowpressure low to moderate current discharges in vapours of alcohols: methanol, ethanol, isopropanol, and n-butanol vapours. These electrical measurements are supported by optical recordings of axial emission profiles from low-current to high-current regimes. The voltage-current characteristics and the corresponding distribution of emission intensities were typically recorded for two pd values, in the left-hand branch of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…[88][89][90][91] The voltage and current characteristics of low-pressure, low to moderate DC current discharges in vapors of alcohols, such as methanol, ethanol, isopropanol, and n-butanol, were reported. 92) Further investigation showed that the effective ionization coefficients for the alcohol vapors were measured by breakdown voltage and emission profile measurements in low-pressure DC discharges. 93) Electron collision cross-sections of dimethyl ether (DME, C 2 H 6 O) were measured under a constant electric field and crossed electric and magnetic fields through the standard swarm analysis.…”
Section: 5mentioning
confidence: 99%
“…[88][89][90][91] The voltage and current characteristics of low-pressure, low to moderate DC current discharges in vapors of alcohols, such as methanol, ethanol, isopropanol, and n-butanol, were reported. 92) Further investigation showed that the effective ionization coefficients for the alcohol vapors were measured by breakdown voltage and emission profile measurements in low-pressure DC discharges. 93) Electron collision cross-sections of dimethyl ether (DME, C 2 H 6 O) were measured under a constant electric field and crossed electric and magnetic fields through the standard swarm analysis.…”
Section: 5mentioning
confidence: 99%